Analysis of Spatially Distributed FU-FB S-ALOHA in Fading Channels Using TUA - Sheikh, Asrar (2007)
The Tagged user analysis (TUA) is a generic approximate method developed to analyze random access protocols for finite-user finite-buffer systems that avoids complexities of Markovian analysis by using available queuing results. In this paper, TUA method is extended to the analysis of finite buffer S-ALOHA operating over flat fading radio channels when the user population is spatially distributed. The expressions for systemperformance indices are derived. It is shown that formoderate number of active users, the simulation and analytical results have a close fit.